2015
DOI: 10.1007/s10973-015-4834-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric analysis of the co-pyrolysis of a bituminous coal and pulp mill sludge

Abstract: Thermal valorization of organic wastes by coprocessing with coal may be a management option for such wastes. In this work, the separate pyrolysis of coal and primary and secondary pulp mill sludge was assessed by thermogravimetric (TG) analysis. Then, under the same experimental conditions, the pyrolysis TG curves of the coal blends with a 10 mass% of either primary or secondary pulp mill sludge were obtained. The corresponding differential thermogravimetry curves made evident that the devolatilization of coal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(42 reference statements)
3
5
0
Order By: Relevance
“…The extent of the synergistic effect varies with the blend ratio of sludge and coal. Notably, the synergistic effect of co-combustion has a differen impact on various temperature ranges, consistent with earlier findings [25,26]. Coimbr al.…”
Section: Thermogravimetric Curve Extractionsupporting
confidence: 91%
“…The extent of the synergistic effect varies with the blend ratio of sludge and coal. Notably, the synergistic effect of co-combustion has a differen impact on various temperature ranges, consistent with earlier findings [25,26]. Coimbr al.…”
Section: Thermogravimetric Curve Extractionsupporting
confidence: 91%
“…Pyrolysis and the accompanying evolution of volatile fractions can be associated with destruction of DSC/mW mg -1 hydrocarbons, partial abstraction of functional groups, formation of simple compounds CO 2 and CH 4 , condensation and polymerization of resulting particles [16][17][18]. In the process of thermal decomposition of pitch-polymer compositions, reactions may occur between decompositions products of CTP and PET.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrolysis is a thermal decomposition of organic compounds at elevated temperatures in an inert environment where the main products are including non-condensable gases, liquid bio-oils as well as solid char (Liu, Song, and Wu, 2015). Potential energy resources in the form of fuels come from the gaseous and liquid products, whereas the solid product may be used as an adsorbent for pollutants removal of contaminated water (Coimbra et al, 2015). Pyrolysis, in addition to being an independent process for producing various chemical compounds and fuels, may also be considered as the initial stage of thermal conversion process of carbonaceous materials, including combustion and gasification (Fang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This process may lead to a variation in the thermal reactivity of the blended materials and on the physical properties and chemical properties of the product generated. Recently, a number of studies have reported the co-pyrolysis characteristics of sludges (Fang et al (2015); Coimbra et al (2015); Xiao et al (2015); Wang et al (2016). Fang et al (2015) studied thermogravimetric analysis of the co-pyrolysis of paper sludge and municipal solid waste through a thermogravimetric simultaneous thermal analyzer from room temperature to 1000 o C. It was reported that with the increase of paper sludge ratio, the mass loss peak was also increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation